Aspects pertaining to the legal regime of Presidential decrees in Romania - Camelia Florentina STOICA; Marieta SAFTA (Juridical Tribune, 2014)
The doctrinal debates on the legal regime of presidential decrees and the recent case-law of the Constitutional Court have determined the present approach for analysis of some aspects pertaining to the issues arising in relation to these acts, especially their legal features and nature and, from this perspective, the differentiations with regard to the challenging of presidential decrees – we refer, in this context, to the extension of the control carried out by courts. The conclusions of the study reveal the importance of addressing and establishing the relations between public authorities, inclusively with regard to the substantiation, issuance and implementation of presidential decrees, in relation to the principle of constitutional loyalty.